2019
DOI: 10.3390/rs11131512
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient In-Situ Debris Flow Monitoring System over a Wireless Accelerometer Network

Abstract: Debris flow disasters pose a serious threat to public safety in many areas all over the world, and it may cause severe consequences, including losses, injuries, and fatalities. With the emergence of deep learning and increased computation powers, nowadays, machine learning methods are being broadly acknowledged as a feasible solution to tackle the massive data generated from geo-informatics and sensing platforms to distill adequate information in the context of disaster monitoring. Aiming at detection of debri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The limited detection of known mass movements to date implies that improved SNR equipment design (e.g., Pankow, 2019, 2020) and preprocessing noise reduction strategies (e.g., Williams et al, 2020) would be of use for deployments in these more exposed areas, and where source amplitudes could be relatively low. Given permitting issues, however, potentially desirous solutions like low-cost and low-power telemetered systems that reduce preparation and installation time (e.g., Schimmel et al, 2018;Ye et al, 2019), may prove challenging to implement. We find that when ASR is correctly operating, some small mass movement events are clearly detectable seismically (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The limited detection of known mass movements to date implies that improved SNR equipment design (e.g., Pankow, 2019, 2020) and preprocessing noise reduction strategies (e.g., Williams et al, 2020) would be of use for deployments in these more exposed areas, and where source amplitudes could be relatively low. Given permitting issues, however, potentially desirous solutions like low-cost and low-power telemetered systems that reduce preparation and installation time (e.g., Schimmel et al, 2018;Ye et al, 2019), may prove challenging to implement. We find that when ASR is correctly operating, some small mass movement events are clearly detectable seismically (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Amplitudes for such events can vary considerably, with reduced pressure observations of 1 Pa at 1 km for small rockfalls and ice avalanches (e.g., Havens et al, 2014;Johnson and Ronan, 2015), to 110 Pa at 1 km for very large avalanches (Allstadt et al, 2017). Machinelearning-based classification and location schemes are increasingly being applied to mass wasting monitoring applications (e.g., Allstadt et al, 2018, and references therein;Ye et al, 2019;Liu et al, 2020;Wenner et al, 2020).…”
Section: Data Processingmentioning
confidence: 99%
“…Huang et al [135] proposed a scheme for debris-flow monitoring that combines a 3D WebGIS-based platform with the WSN, as well as automatic continuous monitoring and early warning of debris flow. Ye et al [136] demonstrated an effective on-site monitoring technique that captures continuous monitoring data through the use of wireless accelerometer sensor networks and cutting-edge machine-learning technologies. Ma [137] employed Bluetooth technology to create a mountain debris-flow health monitoring system, analyse and repair mountain monitoring parts, and build data collecting and processing methods.…”
Section: Internet Of Things (Iot)mentioning
confidence: 99%
“…Ye et al [10] proposed an original monitoring system for detecting debris flow by building a wireless accelerometer network and evaluated it over a mountainous area in Japan. Defining the phenomena of debris flow is challenging because of its drastic ignition and difficult access.…”
Section: Overview Of Contributionsmentioning
confidence: 99%